Pengaruh Likuiditas, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Harga Saham Pada Perusahaan Manufaktur Industri Barang Konsumsi yang Terdaftar di BEI - Mirna Dwi Yanti; Muhammad Salman; Tutie Meutia (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of Liquidity, Sales Growth and Company Size on Share Prices in Consumer Goods Industry Manufacturing Companies in the Food and Beverage Subsector listed on the Indonesia Stock Exchange for the 2013-2022 period. The data analysis methods used are multiple linear regression analysis, t test, F test, and coefficient of determination analysis. Liquidity has a positive and significant effect on share prices in consumer goods industry manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange. Sales growth does not have a significant effect on share prices in consumer goods industry manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange. Company size has a negative and significant effect on share prices in consumer goods industry manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the period. Liquidity, Sales Growth and Company Size simultaneously have a positive and significant effect on share prices in food and beverage sector companies listed on the Indonesian Stock Exchange.